Breast cancer in older patients: national cancer registry data. Issue 7 (13th June 2013) - Sinha, R.; Coyle, C.; Ring, A.
Summary Background The population in developed countries is ageing. Cancer is a disease of ageing, and this is likely to lead to an increase in the number of older patients diagnosed with cancer with significant implications for resource allocation and research priorities. Breast Cancer in older women presents a number of challenges. Aims This paper describes the trends in number of new breast cancer registrations in older patients over the last 38 years. Materials and methods Data were extracted from the Office for National Statistics describing new registrations of breast cancer for patients aged 65 or over, from 1971 to 2009. Results The number of diagnoses of breast cancer across all age groups increased from 17, 694 in 1971 to 40, 260 in 2009. The proportion of diagnoses of breast cancer made in women aged 65 and over increased from 42% in 1971 to 45% in 2009. The proportion of diagnoses of breast cancer made in women aged 70 and over increased from 30% in 1971 to 33% in 2009. The number of cases of breast cancer registered in patients aged 65 and over has increased from 7376 in 1971 to 17, 934 in 2009. Discussion The reasons for the large increases in the number of older women diagnosed with breast cancer, and older women represent an increasing proportion of those diagnosed are multi‐factorial. These include the ageing of the population, obesity, alcohol consumption, use of hormone replacement therapy and reproductive factors, improved breast cancer awareness and the UK National Screening Programme. Clinician attitudes and behaviours and also cancer registries striving to increase their levels are other causes. The effective management of these women will present constraints to service delivery and should therefore influence research priorities. Conclusion This short communication reports on the increasing registration of breast cancer in the older age group which will present a number of challenges for the future.